Synthesis and characterization of innovative GA@Ag-CuO nanocomposite with potent antimicrobial and anticancer properties - Amr H. Hashem; Mostafa A. Abdel-Maksoud; Sabiha Fatima; Saeedah M. Almutairi; Mohamed A. Ghorab; Ahmed I. El-Batal; Gharieb S. El-Sayyad (Scientific Reports)
Abstract Cancer and microbial infections place a significant burden on the world’s health systems and can increase the rate of disease and mortality. In the current study, a novel nanocomposite based on Gum Arabic, silver and copper oxide nanoparticles (GA@Ag-CuO nanocomposite) was synthesized to overcome the problem of microbial infection and in cancer treatment. Characterization using UV-Vis. spectrophotometer reveals that, the observed peak in the spectrum was formed by the observed O.D. at 0.755, and confirmed that the produced GA@Ag-CuO nanocomposite was small and discernible at 360 nm. The particles’ diameters varied from 9.5 nm to 49.5 nm, with a mean diameter of 25.53 ± 1.4 nm. The created Gum Arabic filtrate was rich in active functional groups, and the provided polydisperse NPs were intended to reduce, stabilize, and the produced filtrate act as capping agents. Based on the XRD data, the synthesized GA@Ag-CuO nanocomposite was crystallized and had a face-centered (fcc) crystal structure. Biosafety of GA@Ag-CuO nanocomposite was assessed toward Wi 38 normal cell line, where it showed safety toward the tested cell line where IC50 was 154.2 µg/mL. Antimicrobial results confirmed that, GA@Ag-CuO nanocomposite has antibacterial activity with MICs 15.6, 125, 31.25 and 125 µg/mL against S. epidermis, S. aureus, L. plantrum, and S. typhimurium, respectively. Likewise, it showed antifungal activity toward C. albicans and C. neoformans with MICs 62.5 and 15.62 µg/ml, respectively. Moreover, GA@Ag-CuO nanocomposite displayed promising anticancer activity with IC50 26.11 and 59.5 µg/ml toward MCF-7 and Hep-G2, respectively. In conclusion, the novel GA@Ag-CuO nanocomposite demonstrated promising antibacterial, antifungal, and anticancer activities.